Tinjauan Histopatologi pada Pyoderma Gangrenosum dengan Infeksi Sekunder - Wibisono Nugraha; Danu Yuliarto; Eka Devinta Novi Diana; Alfina Rahma; Prasetyadi Mawardi; Frieda; Ambar Mudigdo (MEDICINUS, 2023)
Background: Pyoderma gangrenosum (PG) is a complex neutrophilic dermatosis, characterized by sterile, painful, necrotic ulcer, and is associated with systemic conditions. PG manifests as papules and vesicles that evolve into painful ulcers. Incidence of PG is relatively rare in Dr. Moewardi Hospital, so it is important to identify and correctly diagnose PG based on its’ histopathological features. Case A 54-year-old man complained of painful scab on several body parts. Hematoxylin and eosin staining in the epidermal layer showed a basket-weave orthokeratosis with necrotic tissue, acanthosis, and basal cell hypermelanosis. In the dermis layer there is a lymphocyte and neutrophil cell infiltrate with slight appearance of leukocytoclastic. Discussion: Pyoderma gangrenosum is a reactive, non-infectious inflammatory dermatosis (neutrophilic dermatoses). In this case, PG occurs in 54-year-old man as painful scab on back and legs. Classical PG characterized by papules, pustules, crusted or necrotic plaque, which typically have undermined, overhanging, dusky purple edges with surrounding induration and erythema. In this patient, the epidermal layer showed ulceration and slight appearance of leukocytoclastic vasculitis in the dermis area and lymphocyte infiltrate with slight neutrophil in the perivascular accompanied by erythrocyte extravasation, which support the diagnosis of PG.